The Role of Discounts in Moderating Impulse Buying on TikTok Shop - Candra Diputra, Kadek Bagus; Saputra, I Made Dena Julio Mahendra (ARRUS Journal of Social Sciences and Humanities, 2025)
This study aims to analyze the role of discounts as a moderating variable between the relationship between social media marketing and shopping lifestyle on impulse buying in TikTok Shop. The study was conducted in Bali, targeting all TikTok Shop users. Through purposive sampling, 245 respondents participated. Data were obtained through questionnaires which were then processed using PLS-SEM. The results show that social media has no influence on impulse buying, while shopping lifestyle has a significant and positive influence on impulse buying, and discounts do not play a role as a moderator between the relationship between social media and shopping lifestyle on impulse buying. Suggestions have been presented in detail below.